Un modèle de la détermination des salaires dans l’industrie de la construction au Québec - Assayag, Abraham; Rabeau, Yves (L'Actualité économique, 1978)
The provincial decree applying to the construction industry in Quebec has created a situation of bilateral monopoly in that segment of the labor market (unions on the supply side and entrepreneurs on the demand side). If negotiations are undertaken at a time where business conditions are booming, then the unions have a very powerful negotiating power. Since contracts are signed for a three year period, wage increases do not afterwards reflect market conditions. Since wages are fixed by the provincial decree, there is then a quantity adjustment in the construction sector. In this paper, we have specified and estimated a model that allows us to measure the bilateral monopoly impact of wage increases and to compute quantity adjustments in the construction market. It is shown then that the provincial decree adversily affects the competition position of the construction industry in Quebec and that restauring this position involves a severe recession in the construction industry.